Study of Efficient Cloud Storage Architectures for the Security Environment - Ayad Hasan Adhab; Naseer Ali Hussien (Journal of Kufa for Mathematics and Computer, 2023)
Lately, cloud computing has acquired notoriety. Data storage is an essential and beneficial area of concentrate in cloud computing. The term "cloud data storage" describes the process of transferring data to an external, up-to-date storage system. You store data to a far-off database instead of your PC's hard plate or another nearby storage gadget. Your PC and the database are associated over the web. The user's requirements for hardware and software are reduced via cloud storage. The security issues associated with accessing and storing data on cloud storage render the cloud information inconsistent and untrustworthy. Through the internet, the cloud computing provides service with dynamically scalable resources. Users gain from cloud computing services in terms of cost and usability. Security issues must be addressed by cloud computing services when sending sensitive data and important applications to shared and public cloud environments. For the needs of data processing and storage, cloud environments are expanding up significantly. The use of cloud computing has a number of benefits as well as drawbacks for service users' data security. The primary security concerns that exist in cloud computing systems are highlighted in this study. The essential security worries with cloud computing are examined in this paper, alongside a straightforward, secure, and protection saving architecture for between cloud data sharing that depends on an encryption/unscrambling calculation that expects to shield data put away in the cloud from unapproved access.